A dissolved organic carbon (DOC) analyzer capable of detecting sub‐μM DOC differences in natural fresh waters: A proof of concept study. (11th May 2018) - Jennings, Meredith; Abdulla, Hussain; Stubbins, Aron; Sun, Luni; Wang, Rui; Mopper, Kenneth
Abstract: This study reports the development of a new type of organic carbon (OC) analyzer that combines flow through analysis and ultraviolet‐wet chemical oxidation (UV‐WCO). Total or dissolved OC (TOC or DOC, respectively) is determined through detection of CO2 as the oxidation product using a vibration insensitive nondispersive infrared (NDIR) gas analyzer. Aided by heat and UV, OC is oxidized by continuously pumping the liquid sample in‐line with a carbon‐free acidic persulfate reagent at a constant flow rate through the system. The CO2 produced from oxidation of OC is sparged from solution at a precise flow rate and is continuously detected, producing a stable signal plateau with high signal‐to‐noise ratio. A low carbon blank/baseline for the analysis is achieved by recycling persulfate reagent alone through the system until minimal CO2 is detected. We show progress in the optimization of this novel instrument that, unlike standard high temperature combustion (HTC) instrumentation that is subject to high blank variability and micromolar resolution (typical coefficient of variation (CV) ∼ 1–2%), has potential applications for studies of DOC net production and consumption by various mechanisms that typically require sub‐micromolar precision.